Hubungan Primipara, Kelainan Putting Susu dan Pekerjaan Dengan Terjadinya Bendungan Asi pada Ibu Menyusui di UPTD Puskesmas Ulak Pandan Kecamatan Semidang Aji Kabupaten Ogan Komering Ulu Tahun 2021 - Ririn Sevda Korini; Yulizar Yulizar; Dewi Ciselia; Chairuna Chairuna (Universitas Batanghari Jambi, 2023)
90% of breast milk dams occur in mothers who give birth for the first time, swelling often occurs on the second to fourth day after delivery. The breasts begin to feel full and hard, causing pain. In the first weeks, if the mother does not get information on how to deal with problems with her breasts, it can cause the mother to stop breastfeeding. Breast engorgement is actually a physiological thing that can be experienced by postpartum mothers but if it does not get good and immediate treatment it can continue to get worse. This study aims to determine the relationship between primiparas, nipple abnormalities and work with the occurrence of breast milk dams in breastfeeding mothers at the UPTD Public Health Center Ulak Pandan, Semidang Aji District, Ogan Komering Ulu Regency in 2021. The design of this study was an analytical survey using a cross sectional research design. The population in this study were all breastfeeding mothers UPTD Ulak Pandan Health Center in 2021, which amounted to 354 people and the number of samples was 80 respondents. The sampling technique used is systematic random sampling. Data analysis used chi square statistical test with p value value (0.05). The results of this study based on the chi square test, it was found that there was a primipara relationship with the incidence of breast milk dams, p value = 0.000 (≤ = 0.05), the relationship between nipple abnormalities and the incidence of breast milk dams was obtained p-value = 0.001 (≤ = 0.05). and the relationship of work with the incidence of breast milk dam p-value = 0.009. (≤ = 0.05). From the results of this study, it is expected to improve the quality of health services for breastfeeding mothers to prevent the occurrence of breast milk dams.